STRATEGI PEMANFAATAN PROGRAM BRIGADE ALAT DAN MESIN PERTANIAN (BAST) - Nila Riska; Didi Rukmana; Rusli M. Rukka (Hasanuddin University, 2020)
The tool and agricultural machinery brigade (BAST), a movement formed between elements of the government, regional government, the ranks of the TNI, farmer institutions and the driving force of agricultural modernization is expected to optimize Alsintan's distribution to farmers. The agricultural machinery and machinery brigade (BAST) program provides another alternative to the lack of use of tools available at the farmer. This research was conducted in Mukti Sari Village, North Luwu Regency. All data and information obtained using the APPAS method (Development Planning Analysis). The results of this analysis indicate that the main problem is that the needs of Alsintan users have not been fulfilled. The main problem is due to a short loan period, there has been no effort in the approach to BAST, and the tool operator is out of focus. This main problem causes the investment of Gapoktan in procuring its own equipment to be low. To solve this problem, we need to fulfill the main objectives, namely the needs of Alsintan users by farmers. This main objective is achieved if the loan lending period increases, there are efforts in the approach to BAST, and the workforce of the operator focuses on work. The main target is to raise Gapoktan investment in the procurement of its own high equipment. The actions needed to achieve the main goal, namely to submit an application for the addition of a loan period, appoint workforce to coordinate with BAST and supervise operator performance. Keywords: Planning, Development, Case.The tool and agricultural machinery brigade (BAST), a movement formed between elements of the government, regional government, the ranks of the TNI, farmer institutions and the driving force of agricultural modernization is expected to optimize Alsintan's distribution to farmers. The agricultural machinery and machinery brigade (BAST) program provides another alternative to the lack of use of tools available at the farmer. This research was conducted in Mukti Sari Village, North Luwu Regency. All data and information obtained using the APPAS method (Development Planning Analysis). The results of this analysis indicate that the main problem is that the needs of Alsintan users have not been fulfilled. The main problem is due to a short loan period, there has been no effort in the approach to BAST, and the tool operator is out of focus.